Bildungstechnologie als pädagogische Wissenschaft und als Lehrobjekt - Strykowski, Wacław (Wydawnictwo Naukowe UAM w Poznaniu, 1992)
The aim of the article is an attempt to present the theoretical and methodological characteristics of educational technology as a pedagogical discipline. The characteristics comprises: the subject of the technology, its functions and its research methods. The article also presents the didactic issues dealt with within the scope of the subject: elements of educational technology, specifying three basic groups of problems: 1) designing of the educational process; 2) preparation of didactic materials; 3) organization of didactic infrastructure.
Educational technology as a pedagogical discipline and as a subject for teaching
Keywords: Metodyka; Methodics; Wizualizacja; Visualisation; Technologia; Technology; edukacja; education